Faktor-Faktor yang Berhubungan dengan Self Efficacy dalam Kegiatan Pembelajaran Siswa SMP Kartini 2 Kota Batam - Cevy Amelia; Rusdani Rusdani; Fauziah Mellinia Wulan Febriani (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2022)
Background: Self-efficacy is a belief in an individual's ability to successfully deal with challenges and have the confidence to achieve their desired outcomes. The purpose of this study was to determine the Factors Associated with Self Efficacy in the Learning Activities of Students in SMP Kartini 2 Batam. Methods: The study uses a descriptive analytic survey research design with cross sectional study approach. The sampling technique was simple random sampling with a sample size of 48 students. Collecting data using a questionnaire sheet and measuring intellectual intelligence with the assistance of a psychologist. Analyzing the data using Spearman's Rho statistics. Results: Spearman's Rho test showed that the experience of success, the experience of others, and psychological conditions had a relationship with self-efficacy, while intellectual intelligence did not. The p-value for experience of success is 0.004, experience of others is 0.039, verbal persuasion is 0.000, psychological condition is 0.007, and intellectual intelligence is 0.823. The correlation coefficient, the experience of success is 0.404, the experience of others is 0.300, verbal persuasion is 0.515, psychological conditions are 0.383, and intellectual intelligence is 0.033. Conclusion: Based on the results of this study, there is a significant relationship between the experience of success, the experience of others, verbal persuasion, and psychological conditions with self-efficacy and there is no significant relationship between intellectual intelligence and self-efficacy. The most influential factor on student learning is verbal persuasion.